Predictors of Rehabilitation Referral Among Cardiovascular Surgical Patients - Gómez González, Laura; Supervia, Marta; Medina-Inojosa, José R.; Smith, Joshua R.; López Blanco, M. Esther; Miranda Vivas, M. Teresa; López-Jiménez, Francisco; Arroyo-Riaño, M. Olga (Frontiers in Cardiovascular Medicine, 2022)
Objective: Cardiovascular disease continues to be the leading cause of mortality globally. Cardiac Rehabilitation (CR) programs act by modifying the evolution of cardiovascular disease and mortality; however, CR programs are under-used. The aim was to determine the profile of patients that received rehabilitation after cardiac surgery. Patients and Methods: A retrospective observational study was conducted from January 2017 to December 2017 at a single center. The study sample was chosen among patients admitted to the Intensive Care Unit of the Hospital Gregorio Marañón / Gregorio Marañón General University Hospital. Socio-demographic and clinical variables were collected. Results: In the present study, 336 patients underwent cardiac surgery of which 63.8% were men and 87.1% had ≥1 cardiovascular risk factor. Of the total cohort, 24.7% were operated for ischemic heart disease, 47.9% valvulopathy, 11% underwent combined surgery, 3.6% cardiac transplantation, 6.5% aneurysms, and 3.9% congenital disease. In-hospital respiratory rehabilitation was prescribed to all patients. Only 4.8% of the patients received motor rehabilitation and 13.8% were referred to CR. We found higher referral rates among patients with more cardiovascular risk factors, <65 years of age, and those undergoing coronary surgery and heart transplantation. Age, ischemic heart disease, and overweight were independent predictors of CR referral. Conclusions: The benefit of CR programs after cardiac surgery is widely described; however, the referral rate to CR remains low. It is crucial to optimize referral protocols for these patients.